Hakekak Insan Monodualistik Perspektif Pendidikan - Abbas Abbas (LPPM IAIN Sorong, 2016)
Man as an individual attempts into reality all his potential, bothphysical and spiritual potential. Physical is the body that is material, palpable, and real. Spiritual or soul is the human element that is spiritual, intangible, can not be touched or captured by the senses. This mental element consists of three types, namely reason, sense, and will. Human beings try to fulfill their own interests or the pursuit of happiness. His action motive is to meet their needs which include physical and spiritual needs, emphasis on self-interest led to individualistic nature within the individual concerned. In addition, in the interests of self-fulfillment factor also makes the individual will be competing for it. Based on the nature of human nature as an individual, it can be seen that man’s dignity, human beings have the basic rights, every human being has a unique potential, and every human being has an interest to meet her needs. On the other hand, people in social groups, such as living state, are bound to the norms as a result of the interaction of man himself. Attachment to the norm is the attachment to respect for others. So, if the individual dimension, emerging basic human rights then in this social dimension, appears fundamental freedoms. The basic obligation of humans being is the respect for basic rights of others and the applicable norms in society. This article describes the position of monolithic humans being.